Carbohydrate nature of lyophilized leaf powder of Azadirachta indica induced inhibition of the activities of accessory reproductive ducts in male rats - G, Usharani; Ghodesawar, Mukhtar Ahmed G; Aladakatti, Ravindranath H (International Multidisciplinary Research Journal, 2013)
Reports have been shown that the chemical nature of leaf powder/extract was carbohydrate-rich in nature. The purpose investigation is designed to investigate the dose dependent effect of carbohydrate nature of lyophilized A.indica leaf powder on some of the androgen dependent biochemical parameters in the reproductive organs which include epididymis (divided in to caput, corpus and cauda), vas deferens, seminal vesicle and ventral prostate of treated rats given 25, 50 and 75 mg in suspension of 1 mL Propylene Glycol, respectively/kg body weight, once daily, orally, for 24 days. Results indicated no significant difference in the body weight of all treated animals. However, there was decreased (P ≤ 0.05) in the weight of accessory reproductive organs. The biochemical analysis showed a dose dependent decrease (P ≤ 0.05) in the total protein content and the activity of acid phosphatase (ACP) and an increase (P ≤ 0.05) in the total free sugar, glycogen, cholesterol contents and the activities of alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) in the reproductive organs of treated rats. Blood serum levels of testosterone, LH and FSH in treated groups were significantly (P ≤ 0.05) reduced respectively when compared to controls. In the present study, the changes in biochemical composition of androgen dependent reproductive organs suggest a deficiency in the level of circulating androgen and decrease in the serum hormone levels in the lyophilized A.indica leaf powder treated animals clearly indicates the action of carbohydrate-rich leaf powder on the secretion of pituitary gonadotropins and inturn in the testosterone biosynthesis in the testis and reproductive organs.